Effects of particle aggregation and disaggregation on their inherent optical properties - Slade, Wayne H.; Boss, Emmanuel; Russo, Clementina (Optics express, 2011)
In many environments a large portion of particulate material is contained in aggregated particles; however, there is no validated framework to describe how aggregates in the ocean scatter light. Here we present the results of two experiments aiming to expose the role that aggregation plays in determining particle light scattering properties, especially in sediment-dominated coastal waters. First, in situ measurements of particle size distribution (PSD) and beam-attenuation were made with two laser particle sizing instruments (one equipped with a pump to subject the sample to aggregate-breaking shear), and measurements from the two treatments were compared. Second, clays were aggregated in the laboratory using salt, and observed over time by multiple instruments in order to examine the effects of aggregation and settling on spectral beam-attenuation and backscattering. Results indicate: (1) mass normalized attenuation and backscattering are only weakly sensitive to size changes due to aggregation in contrast to theory based on solid particles, (2) the spectral slope of beam-attenuation is indicative of changes in PSD but is complicated by instrument acceptance angle, and (3) the spectral shape of backscattering did not provide as clear a relationship with PSD as spectral beam attenuation, as is predicted by theory for solid spheres.